Patient and professional perspectives on physical activity promotion in routine cancer care: a qualitative study - Kadia Saint-Onge; Jany St-Cyr; Isabelle Doré; Lise Gauvin (BMC, 2024)
Abstract Backgrounds Physical activity is associated with many benefits in reducing cancer symptoms and treatments side effects. Yet, studies consistently show that knowledge about physical activity is under-promoted among people diagnosed with cancer. Therefore, we aimed to contribute to filling this gap by ascertaining patient and professional perspectives regarding physical activity promotion. Methods This study took place in Montreal, Canada. We conducted individual, semi-structured interviews with cancer patients who participated in a physical activity program and professionals working in the healthcare system. Participants had to be aged over 18 years, be able to communicate verbally in either English or French, and consent to an audio-recorded interview. A hybrid deductive-inductive approach to content analysis was applied to analyze interview transcripts using Dedoose and Microsoft Excel software. Results Our sample comprised 21 patients (76.2% women) and 20 professionals (80% women). We identified 24 factors (barriers, facilitators, and improvement suggestions) influencing physical activity promotion across organizational, community, and social levels. Results suggest that to improve physical activity promotion in cancer care, it is necessary to showcase exercise specialists as a healthcare resource, to champion for this change within health organizations, to develop partnerships between public and private sectors of the health and fitness industries, and to reassess social norms concerning cancer survivorship and treatment. Conclusion These findings shed light on the gaps and the bright lights in physical activity promotion for people diagnosed with cancer across numerous levels.